Electric vehicles in Sweden : a critical analysis of communication - Parrilla, Assunta (SLU/Dept. of Urban and Rural Development, 2015)
How do the Swedish media talk about electric vehicles? Who are the key players involved and what kind of different discourses do they use? The present research aims at exploring the Electric vehicles discourse in Sweden working with inspiration from critical discourse analysis (CDA) perspective as well as the analysis of how the environmental issue are faced by the Swedish government, how and at what which extent the media talk about EVs and its world. Rather than doing a strict discourse analysis, this analysis explores how social positions become evident in the way actors argue their cases. This analysis is performed with the intent of showing how the Swedish media give more relevance to the economic and political stakeholders by framing the EVs as weaker objects compared to standard vehicles; as a result, the EVs market is being slowed down with the complicity of the government and other stakeholders in favor of standard vehicles and oil companies. In particular, this research focuses on how the information is presented, how words are used, and how the space on newspapers is given or denied, for these elements can reveal many aspects on how the discourse about EVs is built and what kind of interests stand behind. This investigation is focused especially on the text analysis of Swedish newspapers, but includes also interviews, direct observations and participation to seminaries and the analysis of a video commercial. Please note that I am personally in favor of the EV and I believe the reader must know that in order to get a better view of the whole picture.